2012
DOI: 10.2139/ssrn.2187772
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Bank Credit in Small Open Economies: The Case of Six Pacific Island Countries

Abstract: This paper examines the changes in bank credit to private sector across six economies in the South Pacific. An extensive time-series and cross-country panel data allow us to draw new and broader lessons compared to existing research, which have tended to focus mostly on single countries with shorter time periods. Results show that rising average lending and inflation rates may be detrimental to credit growth, and that deposit and asset size contribute positively to credit growth. Results also indicate that str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
6
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 22 publications
4
17
6
6
Order By: Relevance
“…This result differs from what is expected and from what was found by several studies such as Sharma and Gounder (2012). This result can be explained by the lack of the effect of the interest rate of loans on the proportion of credit facilities extended by the Jordanian commercial banks, so the higher inflation rates may lead to an increase in the nominal interest rates on loans, but it does not affect the demand for loans.…”
Section: The Results Of the Regression Analysiscontrasting
confidence: 89%
See 4 more Smart Citations
“…This result differs from what is expected and from what was found by several studies such as Sharma and Gounder (2012). This result can be explained by the lack of the effect of the interest rate of loans on the proportion of credit facilities extended by the Jordanian commercial banks, so the higher inflation rates may lead to an increase in the nominal interest rates on loans, but it does not affect the demand for loans.…”
Section: The Results Of the Regression Analysiscontrasting
confidence: 89%
“…As it is evident in the table, the coefficient ratio of the deposits to the total assets (DEP/TA) was positive but not statistically significant, which means that the proportion of deposits does not affect the ratio of credit facilities granted by the commercial banks in Jordan. This result differs from what is expected and what is fund by the previous studies in this field, such as Sharma and Gounder (2012) and Olokoyo (2011), which indicated that the deposits have a positive impact on the volume of the bank credit. The reason for this result might be resulted from the high liquidity of the Jordanian commercial banks; therefore, they can fund the loans by reducing the portion of the high liquidity.…”
Section: Descriptive Statisticscontrasting
confidence: 99%
See 3 more Smart Citations